Review of Green Food Processing techniques. Preservation, transformation, and extraction. (June 2017) - Chemat, Farid; Rombaut, Natacha; Meullemiestre, Alice; Turk, Mohammad; Perino, Sandrine; Fabiano-Tixier, Anne-Sylvie; Abert-Vian, Maryline
Abstract: This review presents innovative food processing techniques and their role in promoting sustainable food industry. These techniques (such as microwave, ultrasound, pulse electric field, instant controlled pressure drop, supercritical fluid processing) in the frontiers of food processing, food chemistry, and food microbiology, are not new and were already used for > 30 years by academia and industry. We will pay special attention to the strategies and the tools available to make preservation, transformation and extraction greener and present them as success stories for research, education and at industrial scale. The design of green and sustainable processes is currently a hot research topic in food industry. Herein we aimed to describe a multifaceted strategy (innovative technologies, process intensification, bio-refinery concept) to apply this concept at research, educational, and industrial level. Industrial relevance: Green Food Processing could be a new concept to meet the challenges of the 21st century, to protect both the environment and consumers, and in the meantime enhance competition of industries to be more ecologic, economic and innovative. This green approach should be the result of a whole chain of values in both senses of the term: economic and responsible, starting from the production and harvesting of food raw materials, processes of preservation, transformation, and extraction together with formulation and marketing. Highlights: Recent advances in Green Food Processing are detailed. Green techniques enhance processing yield, economy and green impacts. Green techniques act directly in the plant cell to release metabolites. Green techniques are efficient tools for plant-based chemistry.